2021
DOI: 10.3390/nu13114000
|View full text |Cite
|
Sign up to set email alerts
|

Genomics of Postprandial Lipidomics in the Genetics of Lipid-Lowering Drugs and Diet Network Study

Abstract: Postprandial lipemia (PPL) is an important risk factor for cardiovascular disease. Inter-individual variation in the dietary response to a meal is known to be influenced by genetic factors, yet genes that dictate variation in postprandial lipids are not completely characterized. Genetic studies of the plasma lipidome can help to better understand postprandial metabolism by isolating lipid molecular species which are more closely related to the genome. We measured the plasma lipidome at fasting and 6 h after a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 71 publications
(76 reference statements)
0
1
0
Order By: Relevance
“…Similarly, a meta-analysis revealed that higher ABCA1 promoter cg14019050 methylation correlated with lower ABCA1 expression and was concomitantly associated with the C allele of the ABCA1 rs2246293 variant and lower circulating eicosapentaenoic acid [ 17 ]. Genomic, epigenomic, and lipidomic analyses also showed that polymorphisms and methylation sites within the FADS1/2 region influenced the plasma levels of arachidonic acid in response to a high-fat meal in humans [ 18 ]. Of note, genomic assays of post-prandial lipidomic features after dietary fat intake identified potential biomarkers of cardiovascular risk including two polymorphisms in the SORBS1 gene (rs12247017 and rs12240292) affecting b-Sitosterol plasma concentrations [ 19 ].…”
Section: Genomics In Combination Epigenomics Metagenomics Transcripto...mentioning
confidence: 99%
“…Similarly, a meta-analysis revealed that higher ABCA1 promoter cg14019050 methylation correlated with lower ABCA1 expression and was concomitantly associated with the C allele of the ABCA1 rs2246293 variant and lower circulating eicosapentaenoic acid [ 17 ]. Genomic, epigenomic, and lipidomic analyses also showed that polymorphisms and methylation sites within the FADS1/2 region influenced the plasma levels of arachidonic acid in response to a high-fat meal in humans [ 18 ]. Of note, genomic assays of post-prandial lipidomic features after dietary fat intake identified potential biomarkers of cardiovascular risk including two polymorphisms in the SORBS1 gene (rs12247017 and rs12240292) affecting b-Sitosterol plasma concentrations [ 19 ].…”
Section: Genomics In Combination Epigenomics Metagenomics Transcripto...mentioning
confidence: 99%